The Low Temperature Induced Physiological Responses of Avena nuda L., a Cold-Tolerant Plant Species - Wenying Liu; Kenming Yu; Tengfei He; Feifei Li; Dongxu Zhang; Jianxia Liu (The Scientific World Journal)
The paperaim of the was to study the effect of low temperature stress on Avena nuda L. seedlings. Cold stress leads to many changes of physiological indices, such as membrane permeability, free proline content, malondialdehyde (MDA) content, and chlorophyll content. Cold stress also leads to changes of some protected enzymes such as peroxidase (POD), superoxide dismutase (SOD), and catalase (CAT). We have measured and compared these indices of seedling leaves under low temperature and normal temperature. The proline and MDA contents were increased compared with control; the chlorophyll content gradually decreased with the prolongation of low temperature stress. The activities of SOD, POD, and CAT were increased under low temperature. The study was designated to explore the physiological mechanism of cold tolerance in naked oats for the first time and also provided theoretical basis for cultivation and antibiotic breeding in Avena nuda L.